Liquidity Risk and The Impact of Credit Growth on Profitability in Rural Banks: The Moderating Role of Bank Size - Abadi, Andreas Roy Dirgantara; Lutfi, L. (Golden Ratio of Finance Management, 2025)
This study examines how liquidity risk, credit growth, and third-party funding composition influence the profitability of Rural Banks (BPR), with bank size as a moderating factor. Using panel data from 22 conventional BPRs between 2019 and 2023 and applying a fixed-effect regression model, the results show that liquidity management and bank size are closely linked to higher profitability. Credit growth alone, however, is associated with reduced returns, but its interaction with bank size leads to improved performance. This indicates that larger banks are better equipped to handle the risks of rapid credit expansion, while smaller banks may face challenges. The composition of third-party funds shows little direct effect on profitability. The findings carry important practical implications. For bank managers, the results highlight the importance of balancing credit expansion with strong internal controls and prudent risk management, particularly in smaller institutions. Regulators such as OJK are encouraged to consider bank size when designing supervisory frameworks and early warning systems, to ensure sustainable financial performance in the rural banking sector.